1999
DOI: 10.1046/j.1365-294x.1999.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine population structure in an anadromous fish: life‐history influences patterns of mitochondrial DNA variation in the eulachon, Thaleichthys pacificus

Abstract: Due to the apparent decline in size of a number of populations, eulachon, Thaleichthys pacificus, have recently become the focus of a conservation movement in the northeast Pacific. Little is known of the marine life-history phase of this anadromous fish, and although it has been suggested that eulachon spawning in different rivers may form distinct populations, nothing is known of their population structure. Molecular genetic data were used to investigate population structure and possible management schemes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 67 publications
4
20
0
1
Order By: Relevance
“…In our study, fragment A differed the most in terms of the frequency of haplotypes, with AAAAAA showing the lowest frequency and / st value in this forest fragment. The low values of haplotype diversity within samples detected in the current study could be attributed to the predominance of mitotype A (AAAAAA), which was found to occur in frequencies above 76.92% in all the sites (except for the sample from fragment A; Table 4), and the low values of nucleotide diversity could be interpreted as probable close relationships among the haplotypes present within samples, as proposed elsewhere (McLean et al 1999). As for nucleotide diversity, although samples from fragments A and D differed in the number of haplotypes (5 and 3, respectively), both the samples showed similar values of p (around 0.2).…”
Section: Discussionsupporting
confidence: 75%
“…In our study, fragment A differed the most in terms of the frequency of haplotypes, with AAAAAA showing the lowest frequency and / st value in this forest fragment. The low values of haplotype diversity within samples detected in the current study could be attributed to the predominance of mitotype A (AAAAAA), which was found to occur in frequencies above 76.92% in all the sites (except for the sample from fragment A; Table 4), and the low values of nucleotide diversity could be interpreted as probable close relationships among the haplotypes present within samples, as proposed elsewhere (McLean et al 1999). As for nucleotide diversity, although samples from fragments A and D differed in the number of haplotypes (5 and 3, respectively), both the samples showed similar values of p (around 0.2).…”
Section: Discussionsupporting
confidence: 75%
“…Comparable shifts in intraspecific mtDNA diversity associated with the glacial maxima have been documented for several other species (summary by Bernatchez & Wilson 1998). McLean et al . (1999) proposed that eulachon ( Thaleichthys pacificus ) radiated from a single refuge based on low sequence divergence between haplotype groups (0.4%) relative to that of a species which dispersed from multiple refugia [0.7% in rainbow smelt ( Osmerus mordax )] (Bernatchez 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to better understand speciation mechanisms in the marine environment, it is mandatory to characterize not only population dynamics and structure, but also life‐history strategies. At least three competing, but not exclusive, hypotheses may explain population structuring in marine pelagic and demersal fish species (Palumbi 1994; McLean et al . 1999; Avise 2000; Bahri‐Sfar et al .…”
Section: Introductionmentioning
confidence: 99%